2022
DOI: 10.1177/20420986221103918
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy and potential drug–drug interactions among Greenland’s care home residents

Abstract: Background: As lifetime expectancy in Greenland is steadily increasing, so is the proportion of elderly Greenlanders. Old age is associated with polypharmacy, and in this study, we aim to describe the prevalence and characteristics of polypharmacy among the care home residents in Greenland. Methods: Eight care homes in Greenland were visited between 2010 and 2016. Questionnaires including information on prescribed medication and comorbidities were collected and analyzed. Drugs were categorized according to Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
3
1
0
Order By: Relevance
“…However, Faroese women experienced significantly more PIMs and DDIs than men as other studies have reported 48,51 . The mean use of medication among Faroese individuals aged 90 years and older ( n = 6.6) is in line with other studies, for example, a Danish nationwide study that found that individuals >80 years used a median of eight medications, 52 a Swedish study reporting an average use of 6.4 drugs in people aged ≥85 years, 9 and slightly higher than a Greenlandic study where median prescribed drug was six 41 and a US study which reported average 5.9 medications when they turned 90 years 53 . However, few studies among the oldest old report sex‐specific medication use, but in a US study, women took a mean of 6.0 prescription medication and men 5.5 when they turned 90 years, a nonsignificant difference ( p = 0.7), 53 that is, no sex‐difference similar to our finding.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…However, Faroese women experienced significantly more PIMs and DDIs than men as other studies have reported 48,51 . The mean use of medication among Faroese individuals aged 90 years and older ( n = 6.6) is in line with other studies, for example, a Danish nationwide study that found that individuals >80 years used a median of eight medications, 52 a Swedish study reporting an average use of 6.4 drugs in people aged ≥85 years, 9 and slightly higher than a Greenlandic study where median prescribed drug was six 41 and a US study which reported average 5.9 medications when they turned 90 years 53 . However, few studies among the oldest old report sex‐specific medication use, but in a US study, women took a mean of 6.0 prescription medication and men 5.5 when they turned 90 years, a nonsignificant difference ( p = 0.7), 53 that is, no sex‐difference similar to our finding.…”
Section: Discussionsupporting
confidence: 88%
“…This is somewhat expected as morbidity is the primary indicator for medication use and need for nursing home facilities. The observed prevalence of polypharmacy of 74% was in line with or higher compared with other studies, ranging from 63% for residents at nursing homes (median age 77 years) in Greenland, 41 66% in a Danish study of people ≥90 years 42 and 80% in a Swedish study of people aged ≥90 years 43 …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Studies carried out in this area show different results in terms of the percentage of institutionalized elderly people with potential drug interactions. Research carried out in Brazil, Greenland and Spain revealed 25.4%, 61.0% and 81.1% of patients, respectively, with potential interactions [53][54][55], although our data showed more than 90% of the sample with potential interactions underscoring the critical need for vigilant drug management in this population. The differences found in potential drug interactions may be due to the assessment tool used.…”
Section: Discussioncontrasting
confidence: 71%